Baroreflex functionality in the eye of diffusion tensor imaging - Tsai, Ching‐Yi (J Physiol, 2018)
By applying diffusion tensor imaging (DTI) as a physiological tool to evaluate changes in functional connectivity between key brainstem nuclei in the baroreflex neural circuits of mice and rats, recent work has revealed several hitherto unidentified phenomena regarding baroreflex functionality. (1) The presence of robust functional connectivity between nucleus tractus solitarii (NTS) and nucleus ambiguus (NA) or rostral ventrolateral medulla (RVLM) offers a holistic view on the moment‐to‐moment modus operandi of the cardiac vagal baroreflex or baroreflex‐mediated sympathetic vasomotor tone. (2) Under pathophysiological conditions (e.g. neurogenic hypertension), the disruption of functional connectivity between key nuclei in the baroreflex circuits is reversible. However, fatality ensues on progression from pathophysiological to pathological conditions (e.g. hepatic encephalopathy) when the functional connectivity between NTS and NA or RVLM is irreversibly severed. (3) The absence of functional connectivity between the NTS and caudal ventrolateral medulla (CVLM) necessitates partial rewiring of the classical neural circuit that includes CVLM as an inhibitory intermediate between the NTS and RVLM. (4) Sustained functional connectivity between the NTS and NA is responsible for the vital period between brain death and the inevitable cardiac death. (5) Reduced functional connectivity between the NTS and RVLM or NA points to inherent anomalous baroreflex functionality in floxed and Cre‐Lox mice. (6) Disrupted NTS‐NA functional connectivity in Flk‐1 (VEGFR2) deficient mice offers an explanation for the hypertensive side‐effect of anti‐vascular endothelial growth factor therapy (anti‐VEGF) therapy. These newly identified baroreflex functionalities revealed by DTI bear clinical and therapeutic implications.